Fibonacci Sequences Quasiperiodic A5B6C7 Ferroelectric Based Photonic Crystal: FDTD analysis - Simsek, S.; Palaz, S.; Mamedov, A. M.; Ozbay, E. (Advanced Electromagnetics, 2017)
In this study, we present an investigation of the optical properties and band structures for the conventional and Fibonacci photonic crystals (PCs) based on some A5B6C7 ferroelectrics (SbSBr and BiTeCl). Here, we use one dimensional SbSBr and BiTeCl based layers in air background. We have theoretically calculated the photonic band structure and transmission spectra of SbSBr and BiTeCl based PC superlattices. The position of minima in the transmission spectrum correlates with the gaps obtained in the calculation. The intensity of the transmission depths is more intense in the case of higher refractive index contrast between the layers. In our simulation, we employed the finite-difference time domain technique and the plane wave expansion method, which implies the solution of Maxwell equations with centered finite-difference expressions for the space and time derivatives.